CONTROL SYSTEM PATH FOLLOWING FLEXION-EXTENSION MOTION FOR REHABILITATION ROBOT THREE DEGREES OF FREEDOM - Futuhi, Alfi
We address the problem of theraphysts in Indonesia for rehabilitation are limited. Rehabilitation robot is expected to increase the effectivity of rehabilitation process. However, robot rehabilitation has exceedingly dependable behavior itself against stages of patient which makes robot rehabilitation would have specific focus and subject. One of the stages is assisted active movement stage which is aimed for patient who weak and easily hurt against rough and spontaneous external force therefore treatment should have given in smooth and slowly, though patient still has ability to give musle force to the environment. Control design of this rehabilitation robot would be aimed to assist active movement stage of rehabilitation in the future. This control focused on path following system and act as a corrector if error appeared. Design control will continuously convert from angular position to linear position by forward kinematics and otherwise by jacobian inverse kinematics. Researcher uses Proportional Integral (PI) thus stability of system to reach in the desired time. This experiment is done by three conditions specifically: without subject, subject with normal condition, subject with weak condition. In first condition, system has reached one period in flexion-extension motion in 15.25 seconds with response time between each desired point in 1.089 seconds and Mean Squared Error (MSE) value is 0.009194 m2 with x-axis error steady state (essx) is 1.27% and z-axis error steady state (essz) is 10.48%. Second experiment which normal condition has 14.80 seconds in reaching one period flexion-extension motion with response time between each desired point is 0.879 seconds and MSE value is 0.008135 m2 with essx 7.2% and essz 10.63%. For last condition, system has reached on period in flexion-extension motion in 22.67 seconds with response time between each desired point in 1.744 seconds and MSE value is 0.019749 m2 with essx is 7.14% and essz is 11.13%. These results indicate that system has achieved forming flexion-extension motion and fixing the errors gently.